Hydrogen Sulfide: A Key Role in Autophagy Regulation from Plants to Mammalians - Angeles Aroca; Cecilia Gotor (MDPI AG, 2022)
Autophagy is a degradative conserved process in eukaryotes to recycle unwanted cellular protein aggregates and damaged organelles. Autophagy plays an important role under normal physiological conditions in multiple biological processes, but it is induced under cellular stress. Therefore, it needs to be tightly regulated to respond to different cellular stimuli. In this review, the regulation of autophagy by hydrogen sulfide is described in both animal and plant systems. The underlying mechanism of action of sulfide is deciphered as the persulfidation of specific targets, regulating the pro- or anti-autophagic role of sulfide with a cell survival outcome. This review aims to highlight the importance of sulfide and persulfidation in autophagy regulation comparing the knowledge available in mammals and plants.